Pengaruh Agresivitas Pajak Dan Firm Size Terhadap Debt Maturity - Damayanti, Asti Ningrum (Accounting Global Journal, 2022)
Every company will certainly make different decisions in determine and using the debt.and the structure of debt maturity is also something that needs to be considered in depth by the company, this is also related to the survival of the company. If it’s not taken care of properly, it’s feared that the company may go bankrupt. In addition, the maturity structure of the debt can be used as a report on the quality of the company, credibility, and the company's opportunities in the future.This study aims to provide empirical evidence about the tax aggresiveness, firm size, on debt maturity. This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange in the period of 2016 until 2020. Hypothesis testing is done using the Eviews application version 11. There are 49 samples of companies selected using purposive sampling technical using several criteria in accordance with research needs. This study uses a purposive sampling method in determining research samples. Based on test results that tax aggresiveness together affect debt maturity. Partial testing concludes that firm size not affect debt maturity. Keywords: : tax aggressiveness, firm size on debt maturity.